Formulation and organoleptic test of edamame-mackarel tuna sprinkle powder as a high protein supplementation for stunting - Septi Nur Rachmawati; Kareera Aryatika; Dewi Rokhmah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting can also reduce the quality of human resources. Developing regional foods with high protein content, such as edamame and mackerel tuna, can help reduce the prevalence of stunting. Edamame and mackerel tuna were processed into a sprinkle powder. This study aimed to determine the best formulation of sprinkle powder for use as a high-protein supplement. This research was conducted at the University of Jember from January to April 2024 using a completely randomized design at three levels. The experiments were carried out on 25 semi-trained panelists, and proximate tests were analyzed in the laboratory. The results were analyzed using SPSS v24. The results of the statistical analysis of the hedonic test showed that there were no differences in all parameters (color, aroma, taste, and overall) (p > 0,05). The results of the proximate test showed that F3 had the highest water content (9,79±0,1%), ash (9,21±0,09%), and protein (43,18±0,14%), while the highest fat and carbohydrate contents were possessed by F1, 13,21±0,05% and 31,39±0,1%, respectively). In conclusion, the most preferred formulation was F3, and proximate analysis also showed that the highest protein content was found in F3.